2016
DOI: 10.1002/chin.201604093
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Chiral Octahedral Complexes of Co(III) as Catalysts for Asymmetric Epoxidation of Chalcones under Phase Transfer Conditions.

Abstract: The same type of catalyst is found to catalyze the coupling of the obtained epoxide (IIIa) with CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…156 Belokon and co-workers found that octahedral cobalt complexes with chiral O,N,N-donor ligands can conduct the epoxidation of chalcones with 30% aqueous H 2 O 2 (5 equiv) in two-phase media in the presence of inorganic bases. 157 Complex 62 showed the highest enantioselectivity in the series (up to 55% ee). It is worth noting that cobalt salen complexes were tested as catalysts of aerobic olefin epoxidations in the presence of aliphatic aldehydes as sacrificial reductants.…”
Section: Chemical Reviewsmentioning
confidence: 97%
“…156 Belokon and co-workers found that octahedral cobalt complexes with chiral O,N,N-donor ligands can conduct the epoxidation of chalcones with 30% aqueous H 2 O 2 (5 equiv) in two-phase media in the presence of inorganic bases. 157 Complex 62 showed the highest enantioselectivity in the series (up to 55% ee). It is worth noting that cobalt salen complexes were tested as catalysts of aerobic olefin epoxidations in the presence of aliphatic aldehydes as sacrificial reductants.…”
Section: Chemical Reviewsmentioning
confidence: 97%